Comparison between match and training session on biomarker responses in handball players - Nikolovski, Z.; Foretic, N.; Vrdoljak, D.; Maric, D.; Peric, M. (Sports, 2023)
A variety of loads are placed upon an athlete in team sports (e.g., training, match, or competitions). However, the volume of the training load plays an important role in match success. Therefore, the aim of this study was to compare the differences in biomarker dynamics during the match and during training, and to evaluate if such training represents a good stimulus for an athlete to adapt to match stress. Ten male handball players (average age of 24.1 ± 3.17 years, body height of 1.88 ± 0.64 m, and body mass of 94.6 ± 9.6 kg) took part in this study. Their saliva cortisol, testosterone, and alpha-amylase were sampled during the match and training (sessions of 90 min duration, respectively). The results showed that cortisol had higher values after the match (0.65 µg/dL) than after training (0.32 µg/dL) (p = 0.05; ES = 0.39). Testosterone concentrations had a steeper increase during a match (65%) than after training (37%). Alpha-amylase levels did not differ significantly between the match and training (p = 0.77; ES = -0.06). Overall, the results showed that the environment of a match was more stressful for the athletes; therefore, a match provoked a stronger endocrine response in the studied markers. Therefore, we concluded that a match seemed to be a stronger trigger for all of the measured biomarker responses.